Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 199694 by Mingma last updated on 07/Nov/23

Answered by witcher3 last updated on 07/Nov/23

g(x)=f(((x+b)/2))−((f(x)+f(b))/2)  g(a)=0,g(b)=0,rohll theorem  ⇒∃c∈]a,b[∣g′(c)=0;  g′(x)=(1/2)f′(((x+b)/2))−(1/2)f′(x)  g′(c)=0⇔f′(((c+b)/2))=f′(c) applie Rohll to  x→f′(x) over [c,((c+b)/2)] f′′(c)=f′′(((c+b)/2))⇒∃d∈]c,((c+d)/2)[⊂]a,b[  f′′(d)=0

g(x)=f(x+b2)f(x)+f(b)2g(a)=0,g(b)=0,rohlltheoremc]a,b[g(c)=0;g(x)=12f(x+b2)12f(x)g(c)=0f(c+b2)=f(c)applieRohlltoxf(x)over[c,c+b2]f(c)=f(c+b2)d]c,c+d2[]a,b[f(d)=0

Commented by MM42 last updated on 07/Nov/23

very nice   ⋛

verynice

Commented by Mingma last updated on 08/Nov/23

Perfect ��

Commented by witcher3 last updated on 08/Nov/23

Thank You

ThankYou

Terms of Service

Privacy Policy

Contact: info@tinkutara.com